ZnO Nanowire Arrays for Enhanced Photocurrent in PbS Quantum Dot Solar Cells (Adv. Mater. 20/2013). (21st May 2013) - Jean, Joel; Chang, Sehoon; Brown, Patrick R.; Cheng, Jayce J.; Rekemeyer, Paul H.; Bawendi, Moungi G.; Gradečak, Silvija; Bulović, Vladimir
<x xml:space="preserve">Abstract</x> Colloidal quantum dot photovoltaics show great promise for future solar energy conversion applications but remain limited by inefficient charge carrier extraction. Ordered arrays of ZnO nanowires, shown here in blue, can decouple light absorption and carrier collection, yielding a significant relative enhancement in the photocurrent and efficiency of quantum dot solar cells. Further details can be found in the article by Vladimir Bulović and co‐workers on page 2790. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>